Social semiotics comparison between old and new Palestinian mathematics curriculum for the ninth grade - Husam Dawoud; Wajeeh Daher (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2022)
This research aimed to analyze Algebra unit in both the old and new Palestinian curriculum for the ninth grade by using deductive content analysis based on the social semiotic approach. The results of this study showed that, in both books, the mental, behavioral, and verbal processes were more frequent than the relational, existential, and material processes. Moreover, the most frequent object used in both curriculum were the initial description, the rule, and the official definition. The most frequent representation of the mathematical object in both curriculum, was the algebraic representation, then the verbal, the numerical and the graphic representations. The research findings also indicate that in both books, the use of the pronoun “I” was the most frequent, then the pronoun “we” and then other pronouns. The imperative was frequent in the Algebra unit in the old curriculum, but less frequent in the new curriculum. The research findings, regarding the textual function in both books, indicated that the text orientation ‘previous knowledge to new knowledge’ was the most frequent in Algebra. This demonstrates that the author in both books cared about applying the new knowledge and assessing it, what means that the text progresses horizontally in both curriculum.